A standardized workflow for typing S. marcescens outbreaks using FT-IR spectroscopy - Ioannis Passaris; Sam Van Goethem; Florence Crombé; Hannelore Hamerlinck; Stefanie Desmet; Reinout Naesens; Philippe Willems; Deborah De Geyter; Isabel Leroux-Roels; Youri Glupczynski; Surbhi Malhotra-Kumar; Herman Goossens; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Epidemiology and molecular typing of multidrug-resistant bacteria in tertiary hospitals and nursing homes in Flanders, Belgium - Stefanie van Kleef-van Koeveringe; Veerle Matheeussen; Annette Schuermans; Sien De Koster; Natascha Perales Selva; Hilde Jansens; Dieter De Coninck; Katrien De Bruyne; Klaas Mensaert; Marjolein Kluytmans-van den Bergh; Jan Kluytmans; Herman Goossens; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
This study aimed to map MDRO carriage and potential transmission within and between three Flemish tertiary care hospitals and their neighbouring nursing homes. A cross-sectional MDRO prevalence survey was organized between October 2017 and February 2019. Perianal swabs were cultured for detection of MDRO. Determination of clonal relatedness based on wgMLST allelic profiles was performed. The prevalence of MDRO in Belgian hospitals and NHs is on the rise, compared to previous studies, and transmission in and between institutions is observed. These results re-emphasize the need for a healthcare network-wide infection prevention strategy in which WGS of MDRO strains can be supportive.

Incidence and clinical and microbiological features of invasive and probable invasive streptococcal group A infections in children and adults in the Brussels-Capital Region, 2005–2020 - Lisa Zangarini; Delphine Martiny; Véronique Yvette Miendje Deyi; Maya Hites; Evelyne Maillart; Marc Hainaut; Marc Delforge; Anne Botteaux; Veerle Matheeussen; Herman Goossens; Marie Hallin; Pierre Smeesters; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Follow-up blood cultures in Staphylococcus aureus bacteremia: a probability-based optimization - Sam Van Goethem; Hélène Boogaerts; Matthias Cuykx; Pol van den Bremen; Kristien Wouters; Herman Goossens; Hilde Jansens; Gerrit Luit ten Kate (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Performance and ease of use of a molecular point-of-care test for influenza A/B and RSV in patients presenting to primary care - Jan Y Verbakel; Veerle Matheeussen; Katherine Loens; Mandy Kuijstermans; Herman Goossens; Margareta Ieven; Christopher C Butler (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
Annual influenza epidemics cause substantial morbidity and mortality, and the majority of patients with influenza-like illness present to primary care. Point-of-care influenza tests could support treatment decisions. It is critical to establish analytic performance of these platforms in real-life patient samples before uptake can be considered. We aimed to assess the analytical performance and ease of use of the cobas® Liat® PCR POCT in detecting influenza A/B and RSV in samples collected from patients with influenza-like illness in primary care. Sensitivity and specificity of the cobas® Liat® POCT are calculated in comparison with a commercial laboratory-based PCR test (Fast-Track Respiratory Pathogens 21 Plus kit (Fast-Track Diagnostics)). Samples with discordant results were analysed additionally by the RespiFinder 2Smart (PathoFinder) using an Extended Gold Standard (EGS). Acceptability was scored on a five-point Likert scale as well as a failure mode analysis of the cobas® Liat® POCT was performed. Nasal and oropharyngeal swabs were obtained from 140 children and nasopharyngeal swabs from 604 adults (744 patients). The cobas® Liat® POCT had a sensitivity and specificity of 100% (95% CI 99–100%) and 98.1% (95%CI 96.3–99%) for influenza A, 100% (95% CI 97.7–100%) and 99.7% (95%CI 98.7–99.9%) for influenza B and 100% (95% CI 87.1–100%) and 99.4% (95%CI 98.6–99.8%) for RSV, respectively. According to trained lab technicians, the cobas® Liat® POCT was considered easy-to-use, with a fast turn-around-time. Cobas® Liat® POCT is a promising decentralised test platform for influenza A/B and RSV in primary care as it provides fairly rapid results with excellent analytic performance. Point-of-care influenza tests could support treatment decisions in primary care. Cobas® Liat® POCT is a promising decentralised test platform for influenza A/B and RSV in primary care as it provides fairly rapid results with excellent analytic performance.

Quality of molecular detection of vancomycin resistance in enterococci: results of 6 consecutive years of Quality Control for Molecular Diagnostics (QCMD) external quality assessment - Veerle Matheeussen; Katherine Loens; Calum Scott; Caterina Di Lorenzo; Elaine McCulloch; Oliver Donoso Mantke; Herman Goossens; Paul Wallace; Margareta Ieven (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Analytical performance of a platform for point-of-care CRP testing in adults consulting for lower respiratory tract infection in primary care - Veerle Matheeussen; Viviane Van Hoof; Katherine Loens; Christine Lammens; Anouk Vanderstraeten; Samuel Coenen; Chris C. Butler; Paul Little; Theo J. M. Verheij; Herman Goossens; Margareta Ieven (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Increased herpes zoster risk associated with poor HLA-A immediate early 62 protein (IE62) affinity - Pieter Meysman; Nicolas De Neuter; Esther Bartholomeus; George Elias; Johan Van den Bergh; Marie-Paule Emonds; Geert W. Haasnoot; Steven Heynderickx; Johan Wens; Nele R. Michels; Julien Lambert; Eva Lion; et al. (Immunogenetics, 2018)

Evaluation of colistin stability in agar and comparison of four methods for MIC testing of colistin - Agata Turlej-Rogacka; Basil Britto Xavier; Lore Janssens; Christine Lammens; Olympia Zarkotou; Spyros Pournaras; Herman Goossens; Surbhi Malhotra-Kumar (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

The first complete genome sequences of clinical isolates of human coronavirus 229E - Seyed Mohammad Jazaeri Farsani; Ronald Dijkman; Maarten F. Jebbink; Herman Goossens; Margareta Ieven; Martin Deijs; Richard Molenkamp; Lia van der Hoek (Virus Genes, 2012)

National campaigns to improve antibiotic use - Herman Goossens; Didier Guillemot; Matus Ferech; Benoit Schlemmer; Michiel Costers; Marije van Breda; Lee J. Baker; Otto Cars; Peter G. Davey (European Journal of Clinical Pharmacology, 2006)